Eif2b3 mutants recapitulate phenotypes of vanishing white matter disease and validate novel disease alleles in zebrafish. Issue 5 (30th January 2021) - Lee, Yu-Ri; Kim, Se Hee; Ben-Mahmoud, Afif; Kim, Oc-Hee; Choi, Tae-Ik; Lee, Kang-Han; Ku, Bonsu; Eum, Juneyong; Kee, Yun; Lee, Sangkyu; Cha, Jihoon; Won, DongJu; et al.
Abstract: Leukodystrophy with vanishing white matter (VWM), also called Childhood Ataxia with Central Nervous System Hypomyelination, is caused by mutations in the subunits of the eukaryotic translation initiation factor, EIF2B1, EIF2B2, EIF2B3, EIF2B4 or EIF2B5 . However, little is known regarding the underlying pathogenetic mechanisms, and there is no curative treatment for VWM. In this study, we established the first EIF2B3 animal model for VWM disease in vertebrates by CRISPR mutagenesis of the highly conserved zebrafish ortholog eif2b3 . Using CRISPR, we generated two mutant alleles in zebrafish eif2b3, 10- and 16-bp deletions, respectively. The eif2b3 mutants showed defects in myelin development and glial cell differentiation, and increased expression of genes in the induced stress response pathway. Interestingly, we also found ectopic angiogenesis and increased VEGF expression. Ectopic angiogenesis in the eif2b3 mutants was reduced by the administration of VEGF receptor inhibitor SU5416. Using the eif2b3 mutant zebrafish model together with in silico protein modeling analysis, we demonstrated the pathogenicity of 18 reported mutations in EIF2B3, as well as of a novel variant identified in a 19-month-old female patient: c.503 T > C (p.Leu168Pro). In summary, our zebrafish mutant model of eif2b3 provides novel insights into VWM pathogenesis and offers rapid functional analysis of human EIF2B3 gene variants.